Analysis of the effect of incorporating construction and demolition waste on the environmental and mechanical performance of earth-based mixtures. (2nd May 2022) - Paula Junior, Adilson C.; Jacinto, Cláudia; Turco, Chiara; Fernandes, Jorge; Teixeira, Elisabete; Mateus, Ricardo
Graphical abstract: Highlights: Assessment of environmental and mechanical performance of earth-based materials using CDW. A correlation between mechanical strength and environmental impact is established. CDW has shown potential to increase the compressive strength of earth mixtures. CDW can positively contribute to the environmental performance of earth mixtures. Studies on the replacement of binder in earth mixtures with CDW are encouraged. Abstract: In recent years, construction industry has been looking for ways to adopt technical solutions towards environmental preservation and conservation of natural resources. With the scarcity of building materials and the consequent increase in construction prices intensified after the Covid-19 pandemic, sustainable development based on the concepts of the circular economy has become increasingly essential. Meanwhile, the environmental impact associated with most conventional building systems has renewed interest in earth as a building material, combining traditional techniques with technological advancement. The main objective of this work is to understand the environmental and mechanical performance of earth-based mixtures incorporating construction and demolition waste (CDW), filling the gap represented by the absence of review articles that address this new material more comprehensively. The outcomes demonstrated the potential of CDW in improving environmental performance and increasing the compressive strength. Key findings include the need to consider the impact of the transport distance from the waste treatment plant to the construction site in environmental feasibility studies. Results describe the concrete prospect of a construction solution that adapts the environmental and functional advantages of earthen construction to the circular economy model. Further studies on the behaviour of CDW as a substitute for chemical binders are encouraged.